The Characteristics Contract of Syirkah Mudharabah Agreement in The Establishment of a Limited Liability Company - Martoyo, Martoyo; bin Haji Matali, Azme; Eri Safira, Martha (JURNAL AKTA, 2024)
This research is that the forms of business entities in Indonesia and Brunei Darussalam still don’t accommodate a company system based on the provisions of Islamic law, but still rely on agreements underlying the parties in business activities that revolve around a particular product. The integration of Sharia principles in the contract to establish a business entity shows superior values that can be used as guidelines for company management based on Sharia principles. This research aims to find the characteristics contract of syirkah mudharabah contracts which can be used as a form of developing cooperation in agreements to establish limited liability companies. This paper uses normative research methods with a statutory and conceptual approach. The results of this research show that the characteristics of the syirkah mudharabah contract in establishing a limited liability company include 4 (four) things, namely the legal subject or position of the parties in establishing the limited liability company, business capital managed, distribution of profits and losses from collaboration results, and responsibility limited capital owners. This research contributes new findings related to the contracts used in establishing limited liability companies to make them more effective and in line with current Sharia business conditions.